Legal Protection for Victims of Domestic Violence: The Pandemic of Covid-19 - Natasya Nadia Putri; Heru Suyanto (Universitas Kuningan, 2021)
During the pandemic of Covid-19, cases of domestic violence (KDRT) in Indonesia increased. This is because the people experience stress during the pandemic. The stress arises due to the implementation of Large-Scale Social Restrictions (PSBB) set by the Government. In the PSBB period, all normal activities were disrupted, and even affected the economic situation of the community. Accordingly, the researcher discusses the following research problem: The form of legal protection for victims of domestic violence during the Covid-19 pandemic and the factors influence the increase in domestic violence during the pandemic of covid-19. This study employed normative juridical approach. The legal materials in this study were derived from statutory regulations, books, other scientific works, or dictionaries. In conclusion, to impose Large-Scale Social Restrictions (PSBB), the Regional Government needs to review the impact of PSBB on the family. Accordingly, this research is expected to provide an understanding to the public relates to the form of legal protection for everyone who experiences domestic violence during the pandemic. This is stipulated in Law No.23 of 2004 concerning the elimination of domestic violence and the factors influence the domestic violance